PELATIHAN FOTOGRAFI SEBAGAI MEDIA PEMBELAJARAN PENGENALAN BENTUK DASAR VISUAL PADA GURU TK AL MUMIN ASSIDIQIYAH - desintha, siti; Aditya, Dimas Krisna; Fitriani, Fetty (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Learning media for early childhood has various types and functions. At that age is a time when children have excellent grasping. So far, the learning media for the introduction of basic forms applied by Al Mumin Assidiqiyah Kindergarten has not adapted photography. They still use illustration media to introduce basic forms to their students. According to Edgar Dale, photographic images can change the stages of learning, from verbal symbols to more concrete stages, namely visual symbols. So that students can see other realistic visuals and provide alternative learning media. In addition, if you want to use photographic media, the resulting image must meet the elements of form and artistry. Based on this, the PKM team together with the kindergarten as the target community and partners formulated an idea to provide training to teachers on how to recognize basic visual forms through photography techniques in helping teaching and learning activities. This training activity can develop the competence and professionalism of teachers in developing learning media to make it more attractive to students.